2018
DOI: 10.1111/jeb.13222
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of larval competitiveness and associated life‐history traits in response to host shifts in a seed beetle

Abstract: Resource competition is frequently strong among parasites that feed within small discrete resource patches, such as seeds or fruits. The properties of a host can influence the behavioural, morphological and life-history traits of associated parasites, including traits that mediate competition within the host. For seed parasites, host size may be an especially important determinant of competitive ability. Using the seed beetle, Callosobruchus maculatus, we performed replicated, reciprocal host shifts to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 97 publications
1
22
0
Order By: Relevance
“…However, after correcting for body size (i.e., specifying a particular body mass), the authors found that females produced larger eggs in the presence of competition, suggesting that they may produce larger eggs to increase larval survival despite their reduction in body mass. A recent study also conducted with C. maculatus showed that the changes in body size did not occur when beetles were reared on larger seeds, even though female fecundity increased (Fox & Messina, 2018). Here, our findings corroborate those for C. maculatus because differences in body size were not found for A. macrophthalmus despite the observed differences in fecundity.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…However, after correcting for body size (i.e., specifying a particular body mass), the authors found that females produced larger eggs in the presence of competition, suggesting that they may produce larger eggs to increase larval survival despite their reduction in body mass. A recent study also conducted with C. maculatus showed that the changes in body size did not occur when beetles were reared on larger seeds, even though female fecundity increased (Fox & Messina, 2018). Here, our findings corroborate those for C. maculatus because differences in body size were not found for A. macrophthalmus despite the observed differences in fecundity.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study also conducted with C. maculatus showed that the changes in body size did not occur when beetles were reared on larger seeds, even though female fecundity increased (Fox & Messina, ). Here, our findings corroborate those for C. maculatus because differences in body size were not found for A. macrophthalmus despite the observed differences in fecundity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, some sources of selection could be density dependent. Male-male competition is common in high-density populations of C. maculatus (Hotzy & Arnqvist, 2009), and larvae from our Indian source population exhibit particularly strong contest competition within seeds (Messina, 1991; Fox & Messina, 2018).…”
Section: Discussionmentioning
confidence: 99%